Merrytones Tops the Small Bands. - Rampersad, Joan (Newsday)
Merrytones emerged the winner of the Small Bands category at the National Panorama semi-finals, with a total of 277 points. The show went on despite a lack of parking arrangements for patrons at the new Panorama venue. Pan Trinbago president Patrick Arnold admitted that these issues went unnoticed in the planning stages of the competition. Minister of Culture Joan Yuille-Williams however, expressed her satisfaction with the new venue and was comfortable that the show would be enjoyed by all in attendance.
Keywords: Pan Trinbago (Organization); Steel band music -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago; Panorama (Musical festival)